Optimizing HR strategies for sustainable utilization of rural bio-resources: enhancing local communities in India - Jagtap Pujali, Kulkarni Shilpa, Desai Vaibhava (South Eastern European Journal of Public Health, 2024)
ABSTRACT The sustainable utilization of rural bio-resources is crucial for the socio-economic development of local communities in India. This study explores the optimization of Human Resource (HR) strategies to enhance the sustainable use of these resources, aiming to foster community development and enterprise growth. Rural bio-resources, including agricultural produce, forest products, and medicinal plants, present significant opportunities for local economies but are often underutilized due to challenges such as skill gaps, inadequate infrastructure, and limited market access. This research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with stakeholders from various rural bio-resource enterprises across multiple states in India. The findings reveal that targeted HR strategies, such as skills development, leadership training, and employee engagement initiatives, are essential for optimizing the utilization of rural bio-resources. Skills development programs tailored to local needs can bridge the skills gap, while leadership training can cultivate local leaders capable of driving sustainable practices and innovation. Employee engagement and retention are significantly improved through competitive incentives and a supportive work environment. Furthermore, active community involvement in decision-making processes ensures that the benefits of resource utilization are equitably distributed, enhancing socio-economic conditions and community resilience. The study underscores the importance of collaborative efforts among government agencies, private sector entities, and non-governmental organizations to support HR development in rural enterprises. Policy recommendations include increased funding for training programs, infrastructure development, and the integration of digital technologies for remote training and resource management. Continuous monitoring and evaluation of HR strategies are vital to adapt to changing conditions and ensure long-term sustainability. In conclusion, optimizing HR strategies for the sustainable utilization of rural bio-resources can significantly enhance the livelihoods of local communities in India. By addressing the unique challenges faced by rural enterprises through targeted HR interventions, this research highlights a pathway towards sustainable economic growth, environmental conservation, and improved quality of life for rural populations.